A nested case–control study to evaluate the association between fetal growth restriction and vitamin B12 deficiency. (25th February 2013) - Abraham, Anuja; Mathews, Jiji E.; Sebastian, Ajit; Chacko, Kuruvilla P.; Sam, Dibu
Abstract : Objectives: To study the association between maternal vitamin B12 levels and fetal growth restriction. Methods: In this nested case–control study, a cohort of low‐risk women attending the antenatal clinic had their blood samples taken and stored at 28–31 weeks gestation. They were followed until delivery. Fifty‐eight women delivering babies less than 2500 g were taken as cases and an equal number of controls delivering babies more than 2500 g were taken from the same cohort. Their B12 levels were assayed and studied for statistical significance. Results: The baseline characteristics of both groups were similar. The number of women with serum B12 levels less than 200 pg/mL were similar in both groups: 33% versus 29% ( P  = 0.84). Type of kitchen fuel used was taken as a surrogate marker for socioeconomic status. More women in the cases used non‐LPG (liquid petroleum gas) kitchen fuels such as kerosene and wood than in controls, 35% versus 19% ( P  = 0.06). Conclusions: No association between maternal vitamin B12 levels and fetal growth restriction was found in this study. Low birth weight babies were more common in women of low socioeconomic status.